Modern Emergency Management - Cao, Jie (Springer Singapore, 2018)
This book provides essential information on emergency management. It is composed of two parts, addressing the basic theory and related methods of emergency management, including risk management, coordination management, crisis management and disaster management. By putting the emphasis on interdisciplinary, systematic perspectives and building a bridge between basic knowledge and further research, it is well suited as an emergency management textbook and offers a valuable guide to prepare readers for their future emergency management careers.